Best practice in research – Overcoming common challenges in phytopharmacological research. (10th January 2020) - Heinrich, Michael; Appendino, Giovanni; Efferth, Thomas; Fürst, Robert; Izzo, Angelo A.; Kayser, Oliver; Pezzuto, John M.; Viljoen, Alvaro
Abstract: Background: The pharmacology, toxicology and pharmacokinetics of bioactive preparations derived from natural sources has become a flourishing field of research. However, researching complex extracts and natural products faces numerous challenges. More broadly in recent years the critique of pharmacological research, and specifically its design, the methods used and reporting has intensified. Aims: This consensus document provides a perspective on what constitutes best practice in pharmacological research on bioactive preparations derived from natural sources, providing a perspective of what the leading specialist journals in the field consider as the core characteristics of good research. Approach ('methods'): The editors-in-chief of seven journals developed this best practice statement in an iterative process. A first draft of the guidelines (prepared by MH) was then discussed and amended by the other editors. Outcomes: Core to this contribution is a table which provides detailed advice including simple points like a use of appropriate controls and the full taxonomic validity of the material under investigation (see also below), to the relevance of the model for the question being researched ( e.g., can specific in silico or in vitro models really address the species anti-inflammatory activity?). Therefore, obviously, researchers must pay detailed attention to reporting and discussing such studies. This information must be discussed critically (as much as it is possible based on the published papers) in terms of their scientific quality and validity. While these points are obvious, as editors, we are aware that they are often not properly implemented. Conclusion: We call for an approach which incorporates a careful design, meticulous execution and a detailed reporting of studies focusing on the pharmacology/bioactivity of bioactive preparations. Clearly testable research questions must be developed and investigated experimentally. As the founder of pharmacology Claude Bernard put it already in 1865: '…. either the experimenter's hypothesis will be disproved or it will be proved by experiment. When experiment disproves its preconceived ideas, the experimenter must discard or modify it.' Graphical abstract: Image 1